Patterns of Skill Premia - Acemoglu, Daron (Review of Economic Studies, 2003)
This paper develops a model to analyse how skill premia differ over time and across countries, and uses this model to study the impact of international trade on wage inequality. Skill premia are determined by technology, the relative supply of skills, and trade. Technology is itself endogenous, and responds to profit incentives. An increase in the relative supply of skills, holding technology constant, reduces the skill premium. But an increase in the supply of skills over time also induces a change in technology, increasing the demand for skills. The most important result of the paper is that increased international trade induces skill-biased technical change. As a result, trade opening can cause a rise in inequality both in the U.S. and the less developed countries, and thanks to the induced skill-biased technical change, this can happen without a rise in the relative prices of skill-intensive goods in the U.S., which is the usual intervening mechanism in the standard trade models.